Cyclic Amplification of the Afterglow Luminescent Nanoreporter Enables the Prediction of Anti‐cancer Efficiency. (3rd August 2021) - Wang, Youjuan; Song, Guosheng; Liao, Shiyi; Qin, Qiaoqiao; Zhao, Yan; Shi, Linan; Guan, Kesong; Gong, Xiangyang; Wang, Peng; Yin, Xia; Chen, Qian; Zhang, Xiao‐Bing
Abstract: We developed a cyclic amplification method for an organic afterglow nanoreporter for the real‐time visualization of self‐generated reactive oxygen species (ROS). We promoted semiconducting polymer nanoparticles (PFODBT) as a candidate for emitting near‐infrared afterglow luminescence. Introduction of a chemiluminescent substrate (CPPO) into PFODBT (PFODBT@CPPO) resulted in a significant enhancement of afterglow intensity through the dual cyclic amplification pathway involving singlet oxygen ( 1 O2 ). 1 O2 produced by PFODBT@CPPO induced cancer cell necrosis and promoted the release of damage‐related molecular patterns, thereby evoking immunogenic cell death (ICD)‐associated immune responses through ROS‐based oxidative stress. The afterglow luminescent signals of the nanoreporter were well correlated with light‐driven 1 O2 generation and anti‐cancer efficiency. This imaging strategy provides a non‐invasive tool for predicting the therapeutic outcome that occurs during ROS‐mediated cancer therapy. Abstract : An organic afterglow luminescent nanoreporter (PFODBT@CPPO) is developed for visualizing reactive oxygen species (ROS) generation and predicting immunogenic cell death during ROS‐mediated cancer therapy. The thiophene‐based afterglow luminescent nanoplatform is important to develop novel afterglow luminescent materials and provide instant information to avoid adverse immune responses.